Non-steroidal Anti-inflammatory Analgesics for Acute Pain Management in Dogs and Cats - Mathews, Karol A. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
The recently developed non-steroidal anti-inflammatory drugs, discussed in this article, have been shown to be efficacious in controlling post-operative pain, used either alone or in combination with opioids, in both cats and dogs. In some instances selected non-steroidal anti-inflammatory analgesics appear to confer superior analgesia to opioids after orthopedic surgery. However, the side-effects of these drugs are an important factor in selecting the appropriate candidate to receive these analgesics. The contra-indications for use of non-steroidal anti-inflammatory drugs should be strictly adhered to. The trade names listed in this article may differ from those used in individual countries. The reader is advised to consult their own pharmacopea for trade names in the individual’s own country.Recently developed, parenteral NSAIAs have been shown to be effective in managing postoperative pain in cats and dogs. In some instances, individual NSAIAs are equal to, and may be better than, opioid agonists in treating moderate to severe post-operative or medical pain. However, due to the concern for renal failure, gastric ulceration with hemorrhage and hemostatic abnormalities with individual NSAIA administration, caution must be used when selecting patients to receive these analgesics. Indications, relative contraindications and absolute contraindications for NSAIA use are discussed. A pain assessment scale (p. 128) with descriptors and suggestions for pain management are also discussed.
Keywords: Non-steroidal analgesics; cats; dogs; pain